Numerical experiments on the determination of unsteady state temperature distribution in domains of complicated boundary shape. - Laura, P. A. A.; Sánchez Sarmiento, G.; Basombrío, F. G. (North Holland Publishing Co., 1978)
Fil: Laura, P. A. A. Comisión Nacional de Energía Atómica; Argentina